Rizzi, Andrea; Lang, Birgit & Pym, Anthony (2019): What is Translation History? A Trust-Based Approach. Cham: Palgrave Macmillan, 140pp, ISBN 978-3-030-20099-2 - Tang, Xuhua (chronotopos – A Journal of Translation History, 2020)
A review of: Rizzi, Andrea; Lang, Birgit & Pym, Anthony (2019): What is Translation History? A Trust-Based Approach. Cham: Palgrave Macmillan, 140pp, ISBN 978-3-030-20099-2